Role of Surgery and Perioperative Therapy in Older Patients with Resectable Pancreatic Ductal Adenocarcinoma. (4th August 2020) - Xie, Hao; Liu, Junjia; Yin, Jun; Ogden, John R.; Mahipal, Amit; McWilliams, Robert R.; Truty, Mark J.; Bekaii‐Saab, Tanios S.; Petersen, Gloria M.; Jatoi, Aminah; Hubbard, Joleen M.; Ma, Wen Wee
Abstract: Background: It is unclear whether results from recent trials of resectable pancreatic ductal adenocarcinoma (PDAC) are generalizable to older patients, who are underrepresented. We aimed to evaluate outcomes of surgery and of neoadjuvant and adjuvant therapy in older patients with resectable PDAC. Patients and Methods: We included patients aged ≥65 years with upfront resectable PDAC from a prospectively maintained pancreatic cancer registry from 2007 to 2016. Patients were stratified into ages 65–75 and 75+ years. Overall survival (OS) was assessed in treatment comparisons: (A) surgery ( n = 636) versus nonsurgical ( n = 178), (B) neoadjuvant therapy ( n = 139) versus upfront surgery ( n = 497), and (C) adjuvant therapy ( n = 379) versus surgery alone ( n = 118). We compared neoadjuvant ( n = 139) versus adjuvant therapy ( n = 379) in an exploratory analysis. Results: Nine hundred and three patients had a median age of 73.7 (range, 65–96.6) years. Median OS was 26.6 versus 11.9 months (adjusted hazard ratio [HRadj ], 0.4; 95% confidence interval [CI], 0.31–0.52; p < .001) in Comparison A groups, 30.7 versus 25.8 months (HRadj, 0.69; 95% CI, 0.49–0.96; p = .03) in Comparison B groups, and 26.9 versus 17.4 months (HRadj, 0.62; 95% CI, 0.44–0.88; p = .008) in Comparison C groups, respectively. OS benefit in these treatment comparisons was present in age group 75+ with HRadj 0.24 (95% CI, 0.16–0.36; p < .001) in Comparison A and HRadj 0.52 (95% CI, 0.27–1; p = .049) in Comparison B, but not in Comparison C with HRadj 0.68 (95% CI, 0.43–1.08; p = .1). Statistically comparable median OS of patients who received neoadjuvant or adjuvant therapy stratified by age groups was observed. Conclusion: Older patients with resectable PDAC who received surgery, neoadjuvant therapy, or adjuvant therapy appeared to have improved survival outcomes compared with those who did not receive such treatment. Implications for Practice: Older patients with resectable pancreatic ductal adenocarcinoma (PDAC) in general are underrepresented in large clinical trials and less well studied in terms of the role of surgery, neoadjuvant therapy, and adjuvant therapy. This study collected data on older patients with resectable PDAC from a prospectively maintained single‐institutional pancreatic cancer registry of a tertiary referral center from 2007 to 2016. It was found that, with multidisciplinary evaluation, older patients with resectable PDAC who received surgery, neoadjuvant therapy, or adjuvant therapy appeared to have improved survival outcomes compared with those who did not receive such treatment. These results are of substantial importance to practitioners who treat older patients, who are traditionally underrepresented in most clinical trials. Abstract : Most studies that support the benefit of perioperative therapy for resectable pancreatic ductal adenocarcinoma (PDAC) are based on younger patients. This study evaluated the role of surgery, neoadjuvant therapy, and adjuvant therapy in older patients with anatomically resectable PDAC to test the hypothesis that older patients with resectable PDAC who received surgery, neoadjuvant therapy, or adjuvant therapy could have improved survival outcomes compared with those who did not receive such treatments.